Pharmacokinetics and disposition of flupirtine in the horse. (February 2016) - Giorgi, M.; De Vito, V.; Poapolathep, A.; Rychshanova, R.; Sgorbini, M.; Owen, H.
Highlights: Flupirtine IV (1 mg/kg) produced mild and transient side effects in some horses. Flupirtine oral bioavailability was calculated to be 71.4 ± 33.1%. The PO dose simulated to give Cmax and AUC equivalent to the human dose was 2.6 mg/kg. The theoretical effective plasma concentration was calculated to be 187 ng/mL. Abstract: Flupirtine (FLU) is a non-opioid analgesic drug, with no antipyretic or anti-inflammatory effects, used in the treatment of a wide range of pain states in human beings. It does not induce the side effects associated with the classical drugs used as pain relievers. The aim of this study was to evaluate the pharmacokinetic profiles of FLU after IV and PO administration in healthy horses. Six mixed breed adult mares were randomly assigned to two treatment groups using an open, single-dose, two-treatment, two-phase, paired, cross-over design (2 × 2 Latin-square). Group 1 ( n = 3) received a single dose of 1 mg/kg of FLU injected IV into the jugular vein. Group 2 ( n = 3) received FLU (5 mg/kg) via nasogastric tube. The animals then swapped groups after a 1-week wash-out period and the doses were repeated. Blood samples (5 mL) were collected at 0.25, 0.5, 0.75, 1, 1.5, 2, 4, 6, 8, 10, 24, 36 and 48 h and plasma was then analysed by a validated HPLC method. Some mild and transient adverse effects (that spontaneously resolved within 5 min) were observed in 2/6 animals after IV administration. No adverse effects were noticed in the PO administration group. After IV and PO administrations, FLU was detectable in plasma for up to 36 h. The mean elimination half-life was longer after PO (10.27 h) than after IV (3.02 h) administration. The oral bioavailability was 71.4 ± 33.1%. After compartmental simulation/modelling, an oral dose of 2.6 mg/kg was calculated to give Cmax and AUC values in horses similar to those reported in humans after a clinical dose administration with a theoretical FLU effective plasma concentration of 187 ng/mL. These findings may form the basis for further studies concerning this active ingredient in equine medicine.